Asgardians. Volume 2, Thor - O'Connor, George (O'Connor, George. Asgardians, 2024)
"Follow the mighty Thor as he thunders into battle with his trusty hammer, Mjollnir, in hand! His quests take him across fjords, hills, and the blackest Midgard sea to challenge serpents, giants, and more but are these battles and tests of strength more than they seem?"--